A physiologically validated rat model of term birth asphyxia with seizure generation after, not during, brain hypoxia. (18th December 2020) - Ala‐Kurikka, Tommi; Pospelov, Alexey; Summanen, Milla; Alafuzoff, Aleksander; Kurki, Samu; Voipio, Juha; Kaila, Kai
Abstract: Objective: Birth asphyxia (BA) is often associated with seizures that may exacerbate the ensuing hypoxic–ischemic encephalopathy. In rodent models of BA, exposure to hypoxia is used to evoke seizures, that commence already during the insult. This is in stark contrast to clinical BA, in which seizures are typically seen upon recovery. Here, we introduce a term‐equivalent rat model of BA, in which seizures are triggered after exposure to asphyxia. Methods: Postnatal day 11–12 male rat pups were exposed to steady asphyxia (15 min; air containing 5% O2  + 20% CO2 ) or to intermittent asphyxia (30 min; three 5 + 5‐min cycles of 9% and 5% O2 at 20% CO2 ). Cortical activity and electrographic seizures were recorded in freely behaving animals. Simultaneous electrode measurements of intracortical pH, P o2, and local field potentials (LFPs) were made under urethane anesthesia. Results: Both protocols decreased blood pH to <7.0 and brain pH from 7.3 to 6.7 and led to a fall in base excess by 20 mmol·L –1 . Electrographic seizures with convulsions spanning the entire Racine scale were triggered after intermittent but not steady asphyxia. In the presence of 20% CO2, brain P o2 was only transiently affected by 9% ambient O2 but fell below detection level during the steps to 5% O2, and LFP activity was nearly abolished. Post‐asphyxia seizures were strongly suppressed when brain pH recovery was slowed down by 5% CO2 . Significance: The rate of brain pH recovery has a strong influence on post‐asphyxia seizure propensity. The recurring hypoxic episodes during intermittent asphyxia promote neuronal excitability, which leads to seizures only after the suppressing effect of the hypercapnic acidosis is relieved. The present rodent model of BA is to our best knowledge the first one in which, consistent with clinical BA, behavioral and electrographic seizures are triggered after and not during the BA‐mimicking insult.